2020
DOI: 10.3390/en13010281
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gas Composition and Nitrogen Sources of Shale Gas Reservoir under Strong Tectonic Events: Evidence from the Complex Tectonic Area in the Yangtze Plate

Abstract: Strong tectonic movement brings great risk to exploration of shale gas in southern China, especially in Lower Cambrian shale with complex tectonic backgrounds, which has good hydrocarbon-generation matter but low or no gas content. In this paper, the Lower Cambrian shale from the southeast Chongqing region, located in the Upper Yangtze Platform, and the Xiuwu Basin, located in the Lower Yangtze Platform, were selected as the research objects. First, the gas components in shale gas samples were measured, then a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…In addition, the pores were preferentially filled with oil or solid bitumen at the high overmatured stage, so available pore spaces could be declined and gas flow could be restricted [143], resulting in the weak adsorption capacity of CH 4 on OM [166]. Under such a condition, the CH 4 can be easily escaped into shallow surface, while the adsorption capacity of N 2 on OM remains unchanged [167]. Therefore, the N 2 that generated at the late stage of hydrocarbon generation can be easily remained in the shale reservoirs and finally form the shale gas reservoirs with the characteristics of low content of hydrocarbon and high content of N 2 .…”
Section: Factors Controlling Porosity and Gas Content Of The Lower Ca...mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the pores were preferentially filled with oil or solid bitumen at the high overmatured stage, so available pore spaces could be declined and gas flow could be restricted [143], resulting in the weak adsorption capacity of CH 4 on OM [166]. Under such a condition, the CH 4 can be easily escaped into shallow surface, while the adsorption capacity of N 2 on OM remains unchanged [167]. Therefore, the N 2 that generated at the late stage of hydrocarbon generation can be easily remained in the shale reservoirs and finally form the shale gas reservoirs with the characteristics of low content of hydrocarbon and high content of N 2 .…”
Section: Factors Controlling Porosity and Gas Content Of The Lower Ca...mentioning
confidence: 99%
“…Except for few blocks with relatively stable structures in the Sichuan Basin, the Lower Cambrian shales in southern China have undergone strong tectonic deformation, which is considered to be one of major reasons accounting for the low content of natural gas or the enrichment of N 2 in shale gas reservoirs. For example, in the southeastern Chongqing area, on the one hand, relative sliding between hard ground (the underlying Dengying siliceous dolomites) and ductile organic-rich shales (the Lower Cambrian) can lead to the formation of detachment zones due to the compressive stress in the southeast direction [30,167,186,187] (Figure 11); on the other hand, the Lower Cambrian shales were usually uplifted resulting in the formation of numerous thrust faults due to strong tectonic compression. The Lower Cambrian Niutitang shales were usually penetrated into the surface via the faults [167] (Figure 12).…”
Section: Tectonic Deformationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the activity of faults over geologic time may have led to the loss of early generated methane, such that the shale reservoir could be recharged by the late-generated N2-rich gas after the fault was sealed (Gai et al, 2020). Indeed, previous investigations have shown that high concentrations of N2 are generally accompanied by an extremely low overall gas content (< 0.5 m 3 /t) in the lower Cambrian shale reservoirs (Liu et al, 2016;Huang et al, 2019;Wang et al, 2020), suggesting that these shale reservoirs may have experienced long-term methane escape.…”
Section: Metamorphic N2 Flux From Rocks To Gas Reservoir and Surface ...mentioning
confidence: 99%
“…During burial diagenesis and catagenesis, carbon and nitrogen in sedimentary rocks would be lost and converted into hydrocarbons and nitrogen gases, respectively, through thermal and chemical degradation (Behar et al, 2000;Boudou et al, 2008;Gai et al, 2020). Previous studies have suggested several possible sources of N2 in the lower Cambrian shale reservoirs on the Yangtze Block, including atmospheric nitrogen (Huang et al, 2019;Wang et al, 2020) and decomposition of sedimentary organic matter and/or clay minerals (Liu et al, 2016;Gai et al, 2020). The atmospheric origin seems unlikely, because another set of Ordovician-Silurian organic-rich shales on the Yangtze Block does not show a high concentration of N2 (lower than 2.2% on average; Dai et al, 2014).…”
Section: Metamorphic N2 Flux From Rocks To Gas Reservoir and Surface ...mentioning
confidence: 99%